In Vitro Development of Two Species of Orthohalarachne (Acarina: Halarachnidae) and Adaptations of the Life Cycle for Endoparasitism in Mammals - Furman, Deane P.; Smith, Alvin W. (Journal of Medical Entomology, 1973)
Halarachnid mites are parasites of the respiratory tracts of mammals. Two genera typically parasitize marine mammals of the suborder Pinnipedia; species of Orthohalarachne parasitize fur seals and sea lions of the family Otariidae, and the walrus of the family Odobenidae; species of Halarachne are found typically in members of the family Phocidae: gray seal, elephant seal, harbor seal, monk seal and Weddell seal. Occasional reports of Halaraechne species have been recorded from non-pinniped hosts, but these probably represent accidental associations such as that of Halarachne erratica Fain & Mortelmans, 1959, with the Gentoo penguin, Pygoscelis papua (Fain & Mortelmans, 1959, Bull. Soc. Roy. Zool. d'Anvers. 12 : 21–27), or a casual secondary relationship such as the association of Halarachne miroungae Ferris, 1925 with the sea otter (Kenyon, Yunker & Newell, 1965, J. Parasitol. 51 : 960).